2023
DOI: 10.1021/acs.oprd.2c00291
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Tangential Flow Filtration: Process Development and Applications in the Pharmaceutical Industry

Abstract: Tangential flow filtration is an efficient membrane separation technology utilized across a wide range of industries for separation and purification applications. The requirement of telescoped manufacturing to produce high-volume drugs in the pharmaceutical industry has led to increased adoption of membrane separation for drug substance synthesis. Particularly, for noncrystalline molecules with limited product stability and significant thermal liabilities, TFF is a powerful alternative to traditional isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…Rejection ( R ) is normally calculated as a function of the solute concentration in the permeate ( C p ) and retentate ( C r ) by equation , R = ( 1 C p C r ) × 100 % There are many factors affecting the membrane flux and rejection, including the membrane type, solvent system, solute type and concentration, and process parameters (operating temperature, pressure, cross-flow velocity, pH, etc.) . For example, solution concentration is a critical yet often neglected factor in membrane studies.…”
Section: Fundamentals Of Osnmentioning
confidence: 99%
“…Rejection ( R ) is normally calculated as a function of the solute concentration in the permeate ( C p ) and retentate ( C r ) by equation , R = ( 1 C p C r ) × 100 % There are many factors affecting the membrane flux and rejection, including the membrane type, solvent system, solute type and concentration, and process parameters (operating temperature, pressure, cross-flow velocity, pH, etc.) . For example, solution concentration is a critical yet often neglected factor in membrane studies.…”
Section: Fundamentals Of Osnmentioning
confidence: 99%
“…79 In several studies, TFF was demonstrated as an alternative to dead-end filtration, facilitating the sustained maintenance of high flux by minimizing concentration polarization and cake formation. 80 In a study, a modular reactor and in-line TFF microscale system has demonstrated complete substrate conversion, complete enzyme retention and prevention of macromolecule buildup on the membrane. 81 A highly efficient size dependent capturing of circulating tumor cells from a blood sample was demonstrated using an integrated microfluidic system equipped with microfilters of conical-shaped holes, as presented in Fig.…”
Section: Harnessing Microfluidic Technology For Enhanced Bioprocessesmentioning
confidence: 99%
“…During downstream purification (DSP), the purified protein product or drug substance (DS) is transferred from the chromatography elution buffer into the chosen formulation buffer to form the final DP. This is achieved through a combination of buffer exchange and concentration technology consisting of ultrafiltration–diafiltration (UF–DF) steps . The UF–DF technology is highly efficient at low protein concentrations.…”
Section: Introductionmentioning
confidence: 99%